2020
DOI: 10.1371/journal.pone.0241871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the small-scale epidemiology of the stony-coral -tissue-loss-disease in the middle Florida Keys

Abstract: Along the Florida reef tract, stony-coral-tissue-loss disease (SCTLD) has caused extensive mortality of more than 20 scleractinian coral species. The pathogen is unknown, but its epizoology indicates that the disease, facilitated by water currents, has progressed linearly along the tract, affecting reefs at the scale of hundreds of kilometers. To inform ongoing disease mitigation efforts, we examined the small-scale spatial and temporal epidemiology of SCTLD. We established a series of sites in the middle Flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 46 publications
17
48
1
Order By: Relevance
“…Few new cases occurred during the summer months when thermal stress was highest and disease progression slowed considerably. A similar negative correlation was quantified between progression rates of SCTLD and DHW in St. Thomas, United States Virgin Islands (Meiling et al, 2020) and a decline in SCTLD activity coincided with increasing water temperatures in the Middle Keys in 2018, but not in 2019 (Sharp et al, 2020). Within the present study, there appeared to be a threshold at approximately 2-3 • C weeks (DHW) of accumulated thermal stress where the disease stopped progressing, and thus the diseased material in the coral tissue was no longer sloughing off into the water potentially transmitting to new corals as supported by the low incidence values.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Few new cases occurred during the summer months when thermal stress was highest and disease progression slowed considerably. A similar negative correlation was quantified between progression rates of SCTLD and DHW in St. Thomas, United States Virgin Islands (Meiling et al, 2020) and a decline in SCTLD activity coincided with increasing water temperatures in the Middle Keys in 2018, but not in 2019 (Sharp et al, 2020). Within the present study, there appeared to be a threshold at approximately 2-3 • C weeks (DHW) of accumulated thermal stress where the disease stopped progressing, and thus the diseased material in the coral tissue was no longer sloughing off into the water potentially transmitting to new corals as supported by the low incidence values.…”
Section: Discussionsupporting
confidence: 58%
“…Within the present study, there appeared to be a threshold at approximately 2-3 • C weeks (DHW) of accumulated thermal stress where the disease stopped progressing, and thus the diseased material in the coral tissue was no longer sloughing off into the water potentially transmitting to new corals as supported by the low incidence values. These findings could be the result of other seasonal environmental differences not studied here, however, our study and others (Meiling et al, 2020;Sharp et al, 2020) indicate that temperature may have an important influence on SCTLD dynamics. Furthermore, from our observations of physiological signs of stress (bleaching and/or paling) we did not find evidence of thermally stressed corals being more at risk to SCTLD.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Note that total coral mortality data from Port Miami, highlighted in yellow, generally under-performs the regional average of SCTLD loss from all surveys highlighted in light brown. Also, note the consistency of SCTLD impacts by species across all sites irrespective of distance to Port Miami (Precht et al 2016;CSI 2016;DERM 2016;Gintert et al 2019;Hayes 2019;Sinigalliano et al 2019;Sharp et al 2020). (n = 7), coral bleaching (n = 4), competitive mortality (n = 6), and other factors (n = 9) accounted for the mortality of 8.8% of all monitored corals, yet 30.2% (n = 194) of all tagged corals likely died as a direct result of this disease outbreak .…”
Section: The Outbreakmentioning
confidence: 95%
“…Coral rescue goals were to preserve genetic diversity in the Florida population before it was lost to SCTLD and to establish land-based gene banks for future repopulation efforts through translocation of fragments or sexually produced offspring from ex situ facilities to in situ coral nurseries or directly onto reefs. Sharp et al (2020) evaluated the epidemiology of SCTLD as it passed through the middle Florida Keys, identified the existence of intraspecific variability in disease resistance, and suggested that more resilient coral colonies or communities may merit inclusion in future rescue and propagation programs. Thus, future coral rescue efforts from SCTLD endemic areas may continue to occur.…”
Section: Introductionmentioning
confidence: 99%